Women's Dress and the Demise of the Tailoring Monopoly: Farthingale-Makers, Body-Makers and the Changing Textile Marketplace of Seventeenth-Century London. (3rd July 2021) - Bendall, Sarah A.
Abstract : By 1700 tailors no longer dominated England's garment marketplace, as stay-makers, mantua-makers and seamstresses now produced key items of female dress. The demise of the tailoring monopoly was a complex process involving many factors. This article examines an aspect of this transition that has been previously overlooked in histories of garment production: farthingale-makers and body-makers. These trades emerged at the start of the seventeenth century to make foundation garments that shaped the fashionable silhouettes of England's women. This article presents a case study of the number, location, reputation and eventual demise of farthingale-makers and body-makers in the Drapers' and Clothworkers' Companies of London from 1600 to 1700. The story of these trades shows a growing diversification within garment-making during the seventeenth century, where both demand and opportunity allowed entrepreneurial tradesmen to break away from traditional systems of production, ultimately paving the way for the diverse textile marketplace of the eighteenth century.